Perbandingan Risiko Gagal Bayar Perusahaan Penerbit Surat Utang Berperingkat Layak Investasi Berdasarkan Sektor Usaha - Ikhsan, Aulia; Rahadian Fachrur, Aditya; C Permana, Fikri; Nurulhaq Putri, Ayu; Mahendra, Zahra; Panji Wicaksono, Chaesa; Septian, Heggy (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Ratings for debt-issuing companies (issuers) are conducted to provide information on credit quality to investors and prevent default risk, which is the main risk in investing in corporate debt securities. Issuers are generally classified into financial services and non-financial services sectors due to the different risk characteristics between these two sectors. If a company from each sector has the same rating, then the credit quality of both companies will be considered the same. However, research by PEFINDO, S&P, and Fitch shows that the non-financial services sector has a relatively greater potential default risk than the financial services sector. Based on this, this study aims to examine the risk comparison between these two sectors in the investment-grade rating group based on rating transitions and test the assumption that the non-financial services sector has a relatively greater default risk than the financial services sector. The data used in this study are sample data on issuer rating transitions in Indonesia during the period 2007 - 2024 from both sectors. The data analysis technique uses Markov Chains to create a rating transition matrix for both sectors, as well as a comparison test of two proportions using the Z test used to compare the two matrices. A comparison of the transition matrix indicates that the non-financial services sector has a greater probability of default than the financial services sector, with ratings A (0.0078 vs. 0.0045) and BBB (0.0429 vs. 0.0143). Hypothesis testing results indicate that, at the 5% significance level, the non-financial services sector has a greater proportion of rating downgrades than the financial services sector, meaning the risk of default is greater than that of the financial services sector.